2013
DOI: 10.3109/08923973.2013.850506
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 isoforms are differently up-regulated in aflatoxin B1-exposed human lymphocytes and monocytes

Abstract: Our novel findings indicate that AFB₁ more intensively stimulates CYP genes expression in monocytes than in lymphocytes. Mechanistically, this could explain a more pronounced immunotoxicity of AFB₁ in myeloid than in lymphoid lineage cells in vitro/situ/vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 44 publications
1
30
0
1
Order By: Relevance
“…MYO1G was identified in whole blood samples of adult smokers [ 6 , 8 ] but not in PBMC [ 4 ] indicating granulocytes as the main source of this methylation change at this CpG. The enzyme of biotransformation CYP1A1 is rather expressed in metabolic active granulocytes or monocytes than in lymphocytes [ 33 , 34 ]. Additionally, it is of special interest that the smoking-induced hypomethylation at cg19859270 in GPR15+ T cells, representing the adaptive immunity, was never found in cord blood.…”
Section: Discussionmentioning
confidence: 99%
“…MYO1G was identified in whole blood samples of adult smokers [ 6 , 8 ] but not in PBMC [ 4 ] indicating granulocytes as the main source of this methylation change at this CpG. The enzyme of biotransformation CYP1A1 is rather expressed in metabolic active granulocytes or monocytes than in lymphocytes [ 33 , 34 ]. Additionally, it is of special interest that the smoking-induced hypomethylation at cg19859270 in GPR15+ T cells, representing the adaptive immunity, was never found in cord blood.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we aimed to evaluate the neuroimmunotoxic effects of low concentrations of the well-known and potent toxin at the cellular and molecular level in different tissues. We have shown active metabolism of the low level of aflatoxins and its immune dysregulatory effects on different types of human leucocytes [8, 21, 27]. We have also recently shown that murine microglial cells can be activated to produce free radicals and initiate inflammatory responses upon exposure to a low quantity of AFB 1 [9].…”
Section: Discussionmentioning
confidence: 99%
“…The results from this previous study revealed the overexpression of CYP2E1 in Kupffer cells, which induce TLR4 activation, produced inflammatory responses and may lead to liver damage ( 19 ). Under exposure to aflatoxin B1 (AFB1), the observed pronounced increase in TLR4 transcripts in monocytes may be partly attributed to higher expression of CYP1A1 and CYP1B1 caused by AFB1 peroxidation in monocytes ( 20 ). Extracellular signal-regulated kinase (ERK) is downstream of TLR4, and may also be involved in the regulation of DNA methylation patterns by regulating methyltransferase.…”
Section: Introductionmentioning
confidence: 99%